DAMPAK SISTEM PEMBATASAN KUOTA TERDIFERENSIASI BERBASIS NFC DAN TRANSPARANSI TRANSAKSI TERHADAP PERILAKU KONSUMSI SANTRIWATI DI PP DARUSSALAM PUTRI SELATAN - Khafidhotus Sholikhah; Dawimatus Sholihah (Jurnal Ekonomi Syariah Darussalam, 2025)
This study analyzes the impact of a differentiated spending quota system and transaction history transparency based on NFC technology on female students' consumption behavior at Darussalam Putri Selatan Islamic Boarding School. Using a descriptive qualitative approach with a case study method, data were collected through in-depth interviews with 11 informants, 14 days of participatory observation, and documentation study. The findings reveal that spending quotas effectively reduce impulsive purchasing but trigger "social acrobatics" such as card-borrowing and cross-category reallocation as forms of resistance. Meanwhile, transaction history transparency generates a monitoring effect from parents and encourages students' self-evaluation, gradually transforming external compliance into internal financial awareness. This study concludes that the differentiated NFC-based system serves as a more precise consumption control model, yet still requires financial literacy assistance to ensure the sustainable internalization of the value of simplicity (iqtis?d). Keywords: NFC; female students' consumption behavior; financial discipline